LEGALITAS KONTRAK ELEKTRONIK DALAM TRANSAKSI BISNIS DI TINJAU MENURUT UU No. 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Marton Hidayati (Universitas 17 Agustus 1945 Samarinda, 2013)
AbstackThe development of the Indonesian state is an effort to reach the people of Indonesia are just, prosperous, prosperous able to meet the needs of their own people as well as keeping pace sehagai economies of developed countries. To achieve the development targets have been announced by the government, and the role of society indirectly also expected, so the development of the Indonesian state according to what was expected, so the development of the Indonesian state in accordance with what is expected as those set forth in the preamble of the 1945 Constitution.